Portopulmonary hypertension: Still an appropriate consideration for liver transplantation?. Issue 12 (5th November 2016) - Verma, Suman; Hand, Fiona; Armstrong, Matthew J.; de Vos, Marie; Thorburn, Douglas; Pan, Terry; Klinck, John; Westbrook, Rachel H.; Auzinger, Georg; Bathgate, Andrew; Masson, Steven; Holt, Andrew; et al.
Abstract : Liver transplantation (LT) in patients with portopulmonary hypertension (PoPH) has historically resulted in unpredictable and often poor outcomes. The United Kingdom experience for the period 1992‐2012 is reported in this article. A retrospective analysis of patients, preoperatively fulfilling the PoPH European Respiratory Society Task Force on Pulmonary‐Hepatic Vascular Disorders diagnostic criteria was conducted across all UK LT centers. Data collection included comorbidities, use of preoperative and postoperative pharmacotherapy, patient survival, and cause of death. To enable survival stratification, PoPH was classified as mild, moderate, or severe based on mean pulmonary pressure of <35 mm Hg, 35‐49 mm Hg, and ≥50 mm Hg, respectively. Of 127 patients reported to have PoPH, just 28 fulfilled the diagnostic criteria (14 mild, 9 moderate, 5 severe). Twenty (71.4%) patients were male with median age and Model for End‐Stage Liver Disease of 50 years (range, 23‐62 years) and 18 (range, 6‐43), respectively. Twelve (42.9%) patients died within 5 years of LT. The majority of deaths (10 of 12; 83%) occurred within the first 6 months after LT, aetiologies of which included right heart failure (n = 3), progressive PoPH (n = 2), and sepsis (n = 2). Of those receiving preoperative pharmacotherapy (n = 8), 5 are currently alive and were classified as mild to moderate PoPH. Both severe PoPH patients optimized preoperatively with pharmacotherapy died within a year of LT. Development of effective vasodilatory therapies in the setting of pulmonary arterial hypertension has led to a dramatic improvement in patient survival. The available data indicate that in this era of pharmacotherapy, PoPH in isolation no longer represents a valid consideration to transplant. Liver Transplantation 22 1637–1642 2016 AASLD .